Indanthren Dyeings on Rayon (Viscose) Yarn - General Dyestuff Corporation (General Dyestuff Corporation)
Vibrant collection of Indanthren dyings on rayon hanks are included in this mid-20th century sample book published by the General Dyestuff Corporation. Indanthren was the trade name for the first synthetic vat dyes invented in 1901 by René Bohn (1862–1922), a chemist at the Badische Anilin- & Sodafabrik company in Mannheim, Germany. The gatherings of rayon, a synthetic fiber closely similar in structure to cellulose, are dyed using Indanthren. The dye color and recipe is listed next to each gathering.
Keywords: Dyes and dyeing; Rayon; Rayon industry and trade; Samples (Commerce); Textile industry; Textile fabrics; General Dyestuff Corporation